A New Concept of Calcium Carbonate Concrete using Demolished Concrete and CO2 - Maruyama, Ippei; Kotaka, Wataru; Kien, Bui Ngoc; Kurihara, Ryo; Kanematsu, Manabu; Hyodo, Hikotsugu; Hirao, Hiroshi; Kitagaki, Ryoma; Tamura, Masaki; Tsujino, Masato; Fujimoto, Satoshi; Noguchi, Takafumi (Journal of Advanced Concrete Technology, 2021)
Countermeasures against carbon dioxide emissions are a concern in the construction field as well as in society. To solve this problem, a concept for new calcium carbonate concrete is proposed, and this concept is validated experimentally. In the proposed concept, calcium carbonate comprising Ca originating from demolished concrete or other Ca-containing industrial wastes and HCO3- from CO2 gas collected from the air or emitted by industrial plants acts as a binder for aggregates, which can be natural rocks or crushed demolished concrete. This short paper describes the details of the process of making calcium carbonate concrete and discusses future perspectives.